Evaluation of Air Quality in Sudanese Gold Mining Fields (University of Khartoum Engineering Journal, 2022)
This study intended to provide a base line and describe the current air quality in Sudanese Gold mining fields. It covers 21 gold marketing centers in 5 states; namely Northern, River Nile, Gadaref, Red Sea and Kurdofan state. The main objectives of the survey is the detection of any significant concentrations that exceed Occupational Safety and Health norms and specifying the key emission sources, and also identification and assessing of the health hazards and environmental impacts. The tests were carried out by using electronic portable devices to measure the concentrations of pollutants in air. The measured pollutants were: Dust or Particulate Matter (PM), Nitrogen Dioxide (NO2), Volatile Organic Components (VOCs), Sulphur Dioxide (SO2), Ammonia (NH3), Carbon Monoxide (CO) and Ozone (O3). National Ambient Air Quality Standards (NAAQSs) and Sudanese Standards for Ambient Air Pollutants were used for comparison purposes. In addition to that, Air Quality Index (AQI) was applied for the average concentrations of each pollutant. It was found that, all gold marketing centers suffered from very high concentration of PM2.5 and PM10. 90.5% of those centers had higher NO2 concentration than the standards, 37% of it was increased by 200% and 42% of it was increased by 150%. In addition to that, 48% of gold marketing centers had higher SO2 concentration than the standards. On the other hand, concentrations of other pollutants obtained were found within the allowable limits. Finally, it was concluded that all those centers are contaminated with one or more air pollutants. Therefore, it was recommended to improve the environmental conditions by mitigating emissions from point sources. Supervisors have been advised to assume their responsibilities in controlling the use of Personal Protective Equipment (PPE) in addition to the dissemination of safety culture through psychological approach.